Why Nutrition is not improving in Pakistan: an overview of Policy-related, Technical and Professional issues - Hakeem , Rubina (Nurture, 2016)
In spite of contributions by international agencies, Nutrition status of Pakistan has not been improving since several decades. In preceding years focus on nutrition has been greatly enhanced, however likelihood of any significant improvement depends on identification and prevention of pitfalls that restricted progress in the past. Increasing the dose of a wrong medicine is unlikely to cure the disease. This paper reviews the previous activities and attempt to explore the gaps. While nutritional status can be assessed in a variety of ways, sustainable improvement in the nutritional status at the national level is not possible without identifying dietary inadequacies and taking measures to assure adequate food intake. Human nutritionists are expected to have expertise for assessing nutritional status as well as for developing strategies for control of malnutrition. However in Pakistan professionals in the forefront of nutrition related activities lack the expertise to devise appropriate dietary interventions as many of them are neither nutritionists nor dietitians. The nutrition intervention activities in Pakistan are hampered at all levels due to lack of quality control. From conducting of national nutrition surveys to provision of dietary advice, the quality of nutrition activities is affected to the point of threatening health and wellbeing. Without control of quality of nutrition related professional activities, investing in nutrition is like trying to fill the tank with a pitcher having several holes at the base. Hoping to develop and implement effective evidence based strategies in this scenario may remain an unfulfilled dream. Thus in terms of policy, while making any intervention a plan for reducing stunting, assurance of quality of services rendered by team members is required. There is a dire need for a GOP commission that would streamline accreditation of relevant professional nutrition education and training programs, registration of human nutrition professionals and assuring quality of services provided by these professionals.